2021
DOI: 10.3389/fimmu.2021.794770
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-Butylphthalide Rescues Dopaminergic Neurons in Parkinson’s Disease Models by Inhibiting the NLRP3 Inflammasome and Ameliorating Mitochondrial Impairment

Abstract: BackgroundNeuroinflammation and mitochondrial impairment play important roles in the neuropathogenesis of Parkinson’s disease (PD). The activation of NLRP3 inflammasome and the accumulation of α-synuclein (α-Syn) are strictly correlated to neuroinflammation. Therefore, the regulation of NLRP3 inflammasome activation and α-Syn aggregation might have therapeutic potential. It has been indicated that Dl-3-n-butylphthalide (NBP) produces neuroprotection against some neurological diseases such as ischemic stroke. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 78 publications
1
49
0
Order By: Relevance
“…Furthermore, we have demonstrated the involvement of NLRP3 signaling in antipsychotic-induced astrocyte death. Recent findings have revealed that pharmacological blockade of NLRP3 signaling by using salidroside, Dl-3-n-butylphthalide (NBP), gliquidone, or dimethyl fumarate significantly inhibited astrocyte-mediated neuroinflammation, reduced mitochondrial impairment, improved neuronal survival, and slowed the progression of various disease ( Cai et al, 2021 ; Kim et al, 2021 ; Que et al, 2021 ; Tastan et al, 2021 ). Therefore, we suggest that inhibition of NLRP3 signaling may help suppress antipsychotic-induced inflammation and astroglia death.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have demonstrated the involvement of NLRP3 signaling in antipsychotic-induced astrocyte death. Recent findings have revealed that pharmacological blockade of NLRP3 signaling by using salidroside, Dl-3-n-butylphthalide (NBP), gliquidone, or dimethyl fumarate significantly inhibited astrocyte-mediated neuroinflammation, reduced mitochondrial impairment, improved neuronal survival, and slowed the progression of various disease ( Cai et al, 2021 ; Kim et al, 2021 ; Que et al, 2021 ; Tastan et al, 2021 ). Therefore, we suggest that inhibition of NLRP3 signaling may help suppress antipsychotic-induced inflammation and astroglia death.…”
Section: Discussionmentioning
confidence: 99%
“…Recently increasing evidences show that neuroimaging or neuroinflammatory markers are closely related with the pathological neurodegeneration in PD ( Lian et al, 2020 ; Yang et al, 2020 ; Anandhan et al, 2021 ; Li et al, 2021 ; Liu et al, 2021 ; Que et al, 2021 ; Wang et al, 2021 ; Zhu et al, 2021b ). These humoral inflammatory or imaging biomarkers may provide valuable information for early identification, differential diagnosis, assessment of severity and even prognosis prediction for PD patients ( Avenali et al, 2020 ; Beheshti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has suggested that the TLR4/NLRP3 signaling pathways may be the new targets for the development and treatments for depression. The NOD-like receptor family protein 3 (NLRP3) inflammasome complex displays a critical role in the pathogenesis and development of inflammation and immune response ( 11 ). Upon activation, NLRP3 leads to the maturation of the pro-inflammatory cytokines pro-IL-1β and pro-IL-18 ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, NLRP3 leads to the maturation of the pro-inflammatory cytokines pro-IL-1β and pro-IL-18 ( 12 ). Oxidative stress is presumed to activate the NLRP3 inflammasome and contribute to neuroinflammation ( 11 , 13 ). A novel aspect of the immune-inflammation process in the response to stress and depression: the NLRP3 inflammasome is a key molecular mechanism that translates psychological stressful stimuli into inflammatory responses ( 14 ).…”
Section: Introductionmentioning
confidence: 99%